Impact of global warming on potato late blight: risk, yield loss and control - T. KAUKORANTA (Agricultural and Food Science, 2008)
The impact of climate warming on yield losses caused by potato late blight and on the need for disease control was studied by constructing models for timing late blight epidemics and a model of potato growth constrained by late blight. Empirical models predicting the date of planting and emergence of potato were based on thermal time, and a model predicting the date of late blight outbreak was based on thermal time on rainy days. Experiments were conducted over 3 years under ambient and elevated (+3°C) temperatures to obtain parameter values for the growth model. Potato emergence is predicted to occur at 631 degree days accumulated above 0°C after the 16-day running mean temperature in spring exceeds 0°C. A blight outbreak is predicted to occur when the effective temperature sum accumulated above 8°C after potato emergence, on days with at least 0.1 mm of precipitation, achieves 156 degree days. In the prediction of the outbreak the maximum daily accumulation of temperature is limited to 10 degree days. A preliminary sensitivity study carried out at one site in southern Finland suggests that over a range of 1 to 3°C warming, the period during which late blight needs to be controlled by fungicide applications would be 10-20 days longer per 1°C of warming. The increase in yield loss of unprotected crops would be of the same magnitude as the increase in yield potential, around 2 t/ha of dry matter per 1°C of warming.;